The Eye on Mitochondrial Disorders. (April 2016) - Finsterer, Josef; Zarrouk-Mahjoub, Sinda; Daruich, Alejandra
Ophthalmologic manifestations of mitochondrial disorders are frequently neglected or overlooked because they are often not regarded as part of the phenotype. This review aims at summarizing and discussing the etiology, pathogenesis, diagnosis, and treatment of ophthalmologic manifestations of mitochondrial disorders. Review of publications about ophthalmologic involvement in mitochondrial disorders by search of Medline applying appropriate search terms. The eye is frequently affected by syndromic as well as nonsyndromic mitochondrial disorders. Primary and secondary ophthalmologic manifestations can be differentiated. The most frequent ophthalmologic manifestations of mitochondrial disorders include ptosis, progressive external ophthalmoplegia, optic atrophy, retinopathy, and cataract. More rarely occurring are nystagmus and abnormalities of the cornea, ciliary body, intraocular pressure, the choroidea, or the brain secondarily affecting the eyes. It is important to recognize and diagnose ophthalmologic manifestations of mitochondrial disorders as early as possible because most are accessible to symptomatic treatment with partial or complete short-term or long-term beneficial effect. Ophthalmologic manifestations of mitochondrial disorders need to be appropriately diagnosed to initiate the most effective management and guarantee optimal outcome.